2016
DOI: 10.1002/sce.21232
|View full text |Cite
|
Sign up to set email alerts
|

Name-Dropping or Understanding?: Teaching to Observe Geologically

Abstract: This study investigates how teaching can support students' ability to apply rock identification by addressing scientific observation. In the context of geology education in Norway, we investigate two cases in which different approaches to teaching rock identification are carried out. Case A involves traditional teaching activities in one class of upper secondary school students, while Case B consists of teaching activities focusing on observation in a class of elementary school students. The study relies on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
1
8
0
9
Order By: Relevance
“…It is well-known within the literature that school students experience considerable difficulty in coming to understand geological concepts and processes (Francek, 2013;Mills, Tomas, & Lewthwaite, 2016). Research has shown that students have incorrect or incomplete understandings about key ideas such as rock formation and classification (Froyland, Remmen, & Sorvik, 2016), and plate tectonics (Dolphin & Benoit, 2016;Mills, Tomas, & Lewthwaite, 2017), and they struggle to comprehend the vast temporal and spatial scales inherent to learning about geology (Yoon & Peate, 2015). To illustrate, an Australian study that explored middle school students' (n=95) conceptions about geological topics found that students had a limited understanding of plate tectonics, the formation of landforms, and the occurrence of geological events such as earthquakes at tectonic plate boundaries (Mills et al, 2017).…”
Section: Learning About Plate Tectonicsmentioning
confidence: 99%
“…It is well-known within the literature that school students experience considerable difficulty in coming to understand geological concepts and processes (Francek, 2013;Mills, Tomas, & Lewthwaite, 2016). Research has shown that students have incorrect or incomplete understandings about key ideas such as rock formation and classification (Froyland, Remmen, & Sorvik, 2016), and plate tectonics (Dolphin & Benoit, 2016;Mills, Tomas, & Lewthwaite, 2017), and they struggle to comprehend the vast temporal and spatial scales inherent to learning about geology (Yoon & Peate, 2015). To illustrate, an Australian study that explored middle school students' (n=95) conceptions about geological topics found that students had a limited understanding of plate tectonics, the formation of landforms, and the occurrence of geological events such as earthquakes at tectonic plate boundaries (Mills et al, 2017).…”
Section: Learning About Plate Tectonicsmentioning
confidence: 99%
“…Despite this, review articles demonstrate that students of all ages struggle with understanding the nature of rocks, including what a rock is, how rocks can be classified into the major categories, how these categories represent the geological processes that form rocks and the mechanisms driving those processes (American Association for the Advancement of Science, 2015; Cheek, 2010;Dove, 1998;Francek, 2013;King, 2008). Students' alternative conceptions and misunderstandings can partly be ascribed to the strategies they use when classifying rocks (Ford, 2005;Frøyland, Remmen, & Sørvik, 2016;Hawley, 2002). Typically, students sort rock types by choosing superficial features, such as colour or shape, and by comparing and identifying rocks using photographs.…”
Section: Introductionmentioning
confidence: 99%
“…Studier har vist at undervisning utenfor klasserommet kan ha positive effekter på kognitivt laeringsutbytte, sosiale relasjoner, motivasjon, motorisk utvikling og helse (Fjørtoft, 2004;Fägerstam & Blom, 2013;Hartmeyer & Mygind, 2016;Jordet, 2010;Malone, 2008;Rickinson et al, 2004;Waite, 2011). Samtidig har andre studier vist at det å ta elevene ut av klasserommet ikke automatisk bidrar til mer kognitiv laering og forståelse (Brody, 2005;Frøyland, Remmen, & Sørvik, 2016), men at laeringsutbyttet kan økes hvis erfaringene settes i en sammenheng gjennom dialog og tilpasset forarbeid og etterarbeid (Jordet, 2010;Munkebye, 2012;Remmen & Frøyland, 2015;Rickinson et al, 2004). I beskrivelser av miljøundervisning har det ofte vaert en kobling til metoder der det tas utgangspunkt i elevenes naermiljø og lokale miljøutfordringer (Breiting et al, 2009;Sandell & Öhman, 2010;Sandås & Isnes, 2015).…”
Section: Bruk Av Naermiljø Som Laeringsarena I Ubuunclassified